Minimal hepatic encephalopathy: Characteristics and comparison of the main diagnostic modalities - Mumdzhiev, Nikola; Tenev, Rumen V.; Radicheva, Mariana P. (Clinical and Experimental Hepatology, 2024)
According to the latest clinical guidelines, minimal hepatic encephalopathy (MHE) is diagnosed by using a single test for which the center has experience and local norms. Nowadays, several tests are available. Here we describe the most frequently used tests: Psychometric Hepatic Encephalopathy Score (PHES), Continuous Reaction Time (CRT), Inhibitory Control Test (ICT), Stroop test, Animal Naming Test (ANT), critical flicker frequency (CFF) and electroencephalography (EEG) using characteristics such as: creation specificity, neurocognitive domains, computerized vs. pencil and paper, translatability, time to perform, learning effect, affecting factors, local norms, copyright, medical equipment and need for specific training. After that we briefly address comparison of the results of different tests or test combinations. Such information may prove useful to anyone new to the field of minimal hepatic encephalopathy.